An unusual case of myiasis - Ahmed Messahel; Pinaki Sen; Ajay Wilson; Manu Patel (Elsevier, 2010)
Summary: Myiasis-the feeding of fly larvae on living mammals, may have various clinical presentations depending on the tissues or organs involved. Myiasis is a common travel associated skin disorder as a consequence of short visits to developing countries. It is the fourth most common travel associated disease. The most common clinical manifestations of fly larvae infestation include inflammatory and allergic reactions. Ear, eye and respiratory tract infestations are not uncommon and the human botfly Dermatobia hominis is the most recognised causative organism. We present an unusual case report of a myiasis in the upper lip of a patient admitted under the maxillofacial team at South Manchester Hospital. Keywords: Upper lip infestation, Myiasis